Moral Values for the National Character Building in Novel “The Rainbow Troops” - ahmad saifudin (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
This study is to identify the moral values that can be implemented to build students’ character in the novel “The Rainbow Troops”. The research method was qualitative research with intertext approach. The role of the researcher is a compulsory because the researcher is the key instrument in this study. The finding in this research is found fourteen moral values or more than a half number of moral values that were promoted by Kemendiknas in the year 2010. One of them is the dominant, it is empathetic. Two of them are the moderate number; they are religious and sportive and respectful values. The others are the low number; they are disciplined, hard-working, creative, independent, democratic, curious, patriotic, inclusive and communicative, peace-loving, studious, and responsible. All of them can be used to build student’s character.